“Incidencia de las manifestaciones orales en pacientes con diabetes mellitus que acuden al centro de salud de guano, provincia de Chimborazo” - Pilataxi Acalo, Jessica Paulina (2017)
The main objective of the research project is to determine the incidence of the main pathologies in Canton Guano patients, in the Public Health Center, there is the Diabetic Club, whose patients are part of the general care; However, a technique for the prevention and promotion of oral health for diabetics, which improves the quality of life in patients with the aforementioned systemic pathology, has not been determined. In what constitutes oral health, there are shadows that can manifest themselves. Product of the pathological condition they carry; For this reason, this research intends to implant the levels of prevention and promotion in patients with diabetes who go to the health center of Guano of the Province of Chimborazo, performing the early identification of the oral manifestations that cause a cause of diabetes. The research was of the transversal type; Since its respective application was made in the period January - April 2017. Authorization was requested to review the medical history and collect data to identify how many years presented systemic pathology. The results obtained after this investigation showed in response to the following data: With respect to oral pathologies it is observed that there was more affectation in type 2 diabetes, resulting in the higher grade, followed by gingivitis affecting 37, 36 patients Presented periodontitis, 31 patients had xerostomia, 17 presented alterations of taste, 8 had candidiasis and the pathologies that none of the patients presented 0% were oral ulcers, lingual fissures, burning mouth and rhomboid glossitis.